Not your unicorn: trans dating app users' negotiations of personal safety and sexual health. Issue 1 (2nd January 2021) - Albury, Kath; Dietzel, Christopher; Pym, Tinonee; Vivienne, Son; Cook, Teddy
ABSTRACT: This article reflects on 14 Australian trans dating app users' accounts of feeling safer (and less safe) when using apps, as well as their experiences of sexual healthcare. We explore both app use and healthcare in the context of the interdisciplinary field of 'digital intimacies', considering the ways that digital technologies and cultures of technological use both shape and are shaped by broader professional and cultural norms relating to sexuality and gender. Drawing on Preciado's [(2013). Testo junkie: Sex, drugs and biopolitics in the pharmacopornographic era . The Feminist Press] framework of 'pharmacopornographisation', the analysis aims to contextualise participants' experiences of being 'seen' and 'known' by health professionals and other app users. Our findings indicate that both dating apps and sexual health services rely on reductive systems of sorting and categorisation that reinforce binary understandings of genders and sexualities in order to facilitate data management and information sharing practices. Yet these same sorting and filtering technologies can also help trans app users avoid harassment, form intimate connections and seek appropriate healthcare.